THE RISE OF INDIA IN THE NEW BALANCE OF POWER IN ASIA SINCE THE BEGINNING OF 21ST CENTURY: IMPACTS ON INDIA - VIETNAM RELATIONS - Nam Tien, Tran (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The study focuses on the rise of India in the new balance of power in Asia since the beginning of the 21st century. It had three major purposes: (a) to discover the new balance of power in Asia (b), to examine the possible predicting scenario about the role of India in Asia’s order; (c) to understand critical influences of the Indian rise that affect on India-Vietnam relations. Methodology: This study describes a qualitative study based upon a combination of three main methods such as historical method, analysis-synthesis method (documentary analysis), and case study method. The data were sourced from secondary data and content analysis in various publications of governments, foreign governments, or international bodies. Moreover, foreign policy journals, books, magazines, newspapers, and public records. Main Findings: The study had some key research findings. The first main finding was that the rise of India would contribute to the common development of Asian countries and affirm the position of Asia on the world map. The second major finding was that India-Vietnam relationships supported India becoming a peaceful superpower dominating East Asia, especially Southeast Asia. Applications of this study: The implications of the study can be supported by the observation of foreign policy substitutability. This study about the rise of India can be used to get the support of the policymaker or government to make the foreign policy adapting to the new era in Asia. Moreover, the study is also a valuable document for students majoring in International Relations, International History, and Politics. Novelty/Originality of this study: There is no or has not been any study that discusses the rise of India in the new balance of power in Asia since the beginning of the 21st century and its impacts on India-Vietnam relations.